Exploring the Intersection of Digital Forensics and Neural Networks: A Decade-Long Analysis - Effendi, Muhammad Imam; Purwaningsih, Sri Budi; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This comprehensive dataset sourced from Lens.org focuses on digital forensics and neural networks, spanning scholarly articles from 2002 to 2012. With 476 curated journal articles, our study refined to 16 pertinent law-related articles using advanced search filters. The goal was to illuminate key trends in this dynamic realm, highlighting institutions like University of Westminster and University of Texas at San Antonio, active years in 2007 and 2012, and the prevalence of computer science as the primary field of study. Notable works, like "An automated timeline reconstruction approach for digital forensic investigations" by N Lang Beebe and J Guynes Clark in 2016, were identified. Our findings provide nuanced insights, shaping future discourse on the interdisciplinary nexus between digital forensics and neural networks. Highlights : Dataset covers digital forensics and neural networks from 2002 to 2012 Key trends include prominent institutions, active years, and primary study fields Offers valuable insights for shaping future discourse in this interdisciplinary field Keywords: Digital Forensic, Neural Networks, Law, Interdisciplinary, Trends